ANALISIS STRATEGI MANAJEMEN KELAS UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI KELAS IV UPT SDN 018 LANGGINI - Putri April Yanti; Nasrul; Masrul; Nurmalina; Zulhendri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of classroom management strategies and the effectiveness of learning through the application of classroom management strategies in Grade IV at UPT SD Negeri 018 Langgini. Classroom management is considered an important factor in creating a conducive learning atmosphere so that learning objectives can be achieved optimally. This research employs a qualitative approach with a field research design. The research subjects consisted of the class teacher and Grade IV students. Data were collected through observation, interviews, and documentation, and the validity of the data was ensured through source and technique triangulation. The results indicate that classroom management strategies were implemented through four aspects: planning, organizing, leadership, and classroom control. The teacher prepared learning tools, arranged seating and learning time, motivated students, and enforced classroom rules and discipline. Learning effectiveness was categorized as quite effective, as most students were active and focused during learning activities. However, some students were still less active and less disciplined, causing learning to be not yet fully optimal. Thus, classroom management strategies play an important role in improving learning effectiveness, although improvements are still needed in classroom control and student motivation.Keywords: : Classroom Management, Learning Effectiveness, Elementary School.This study aims to analyze the implementation of classroom management strategies and the effectiveness of learning through the application of classroom management strategies in Grade IV at UPT SD Negeri 018 Langgini. Classroom management is considered an important factor in creating a conducive learning atmosphere so that learning objectives can be achieved optimally. This research employs a qualitative approach with a field research design. The research subjects consisted of the class teacher and Grade IV students. Data were collected through observation, interviews, and documentation, and the validity of the data was ensured through source and technique triangulation. The results indicate that classroom management strategies were implemented through four aspects: planning, organizing, leadership, and classroom control. The teacher prepared learning tools, arranged seating and learning time, motivated students, and enforced classroom rules and discipline. Learning effectiveness was categorized as quite effective, as most students were active and focused during learning activities. However, some students were still less active and less disciplined, causing learning to be not yet fully optimal. Thus, classroom management strategies play an important role in improving learning effectiveness, although improvements are still needed in classroom control and student motivation.